VISUALIZATION OF REAL PHYSICAL PROCESSES USING 3D-EDITOR BLENDER - Kassenova, Л.Г.; Yessekeyeva, М.Ж.; G.S. , Г.С. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2021)
In the context of Informatization of society, much attention is paid to the use of information and communication technologies in the educational process. The younger generation of the information society are people of dynamic information on the screen. Information on the screen of a monitor, projector or TV is perceived by them much better than printed, book information. The use of information technologies in the educational process makes it possible to improve the quality of classes, to get interested in the problem, as well as to visualize the material, visually presenting phenomena that can not be demonstrated otherwise. Modern technical and software tools allow you to create and use educational models of objects and processes that are as close to reality as possible. The combination of both graphic and audio information provides an impact on the two most important sensory organs-vision and hearing, which significantly increases the information content of the educational process and the effectiveness of its perception. The computer models presented in the article can be used in the educational process of the University for elective courses and electives of physical and technical orientation.